The Challenges of the Kurikulum Merdeka Implementation in 3T Area - Tomasouw, Jolanda; Marantika, Juliaans E R; Wenno, Eldaa Crystle; van Delzen, June Carmen Noya (KnE Social Sciences, 2024)
This study investigates the challenges of implementing the Kurikulum Merdeka in the disadvantaged, remote, and outermost (3T) areas of Maluku. The significance of this research lies in addressing the geographic, infrastructural, and educational accessibility issues in these 3T areas, which can hinder the effective implementation of the Curriculum. The research employs a descriptive qualitative methodology. The study engaged 40 respondents, including school principals, teachers from both public and private schools, training facilitators, and assistant program implementers. Data were collected through questionnaires and interviews and were then analyzed to identify recurring patterns, problems, challenges, and obstacles faced during implementation. The results indicate that despite their dedication to implementing the curriculum, nearly all schools struggle with the execution of the Kurikulum Merdeka. The main challenge identified is the inadequacy of teachers in designing and carrying out learning activities as required by the curriculum. This issue arises from various factors, including limited access to technology, insufficient training for principals and teachers, shortcomings in the mentoring mechanisms, and a lack of digital literacy among educators. Consequently, the government's mandate to implement this curriculum in all schools should be preceded by comprehensive preparation. Emphasis should be placed on enhancing teachers' capabilities through training sessions and workshops focused on planning, executing, and evaluating learning activities. Additionally, providing sufficient facilities and fostering a supportive learning environment are essential aspects that must be addressed. Keywords: implementation, Kurikulum Merdeka, disadvantaged, remote area